Comparative Analysis Using the SCAPS-1D Software on the Stability and Toxcity of the Perovskites FAPbI3, and FASnI3 - Touré Sékou; Amal Bouich; Youssouf Doumbia; Bernabé Marί Soucase (Advanced Energy Conversion Materials, 2024)
Hybrid organometallic perovskites such as FAPbI3 (formamidinium lead iodide) and FASnI3 (formamidinium tin iodide) are recognized as promising materials for the next generation of high-efficiency solar cells. FAPbI3 is particularly valued for its stability and excellent optoelectronic properties. However, the toxicity of lead and the resulting environmental concerns drive the search for alternatives like FASnI3, where tin, a less toxic and more abundant element, replaces lead, which is the objective of this study. The lead-free structure simulated using SCAPS-1D software is as follows: FTO/TiO2/FASnI3/Spiro-OMeTAD/Ag. We opted for TiO2 as the ETL due to its wide bandgap ( 3.2 eV for the anatase phase), which effectively blocks holes and prevents their recombination with electrons, thus promoting better charge separation. Moreover, the favorable energy level alignment of TiO2 with the perovskites facilitates the transfer of electrons to the silver (Ag) electrode. For the HTL, we chose Spiro-OMeTAD, whose valence band level is well aligned with that of the perovskites, making it easier to extract holes to the upper silver electrode. Using the SCAPS-1D simulator, we then compared the electrical and optical properties of the devices, focusing on key parameters such as short-circuit current density (Jsc), open-circuit voltage (Voc), fill factor (FF), and power conversion efficiency (PCE). The best results obtained after optimizing the aforementioned parameters are Jsc of 30.65 mA/cm2, Voc of 0.8469 V, FF of 86.63%, and PCE of 22.49%. The research presented here shows that optimizing several parameters can achieve a power conversion efficiency (PCE) of 22.49%. Additionally, the structure studied in this article could be a good candidate for future research on lead-free perovskite solar cells.